Compulsory licensing of pharmaceuticals during public health crisis: a TRIPS framework analysis - Li, Zhanpeng; Guo, Peng (Frontiers in Public Health, 2025)
The COVID-19 pandemic has exposed inequities in global healthcare resource allocation, reigniting debates over international intellectual property (IP) protections. Among existing flexibility mechanisms, the TRIPS Agreement’s compulsory licensing provisions serve as a critical tool to ensure access to essential medicines. Member states can invoke Article 31(b)'s “national emergency” or “other circumstances of extreme urgency” clauses to utilize patented Pharmaceuticals for public health emergencies without prior authorization, a mechanism already effectively employed by multiple nations during the pandemic. However, due to procedural complexities and potential trade disputes associated with TRIPS, some developing countries have advocated for temporary IP waivers as an alternative solution. It must be emphasized that compulsory licensing retains unique value in balancing public health needs with IP protections. To better prepare for future health crises, improvements to the TRIPS compulsory licensing tool could focus on two priorities: prioritizing essential medicine accessibility over price control objectives, and enhancing local pharmaceutical production capabilities in developing nations.